Usefulness of differential somatic cell count for udder health monitoring: Effect of intramammary infections, days in milk, quarter location, and parity on quarter-level differential somatic cell count and somatic cell score in apparently healthy dairy cows - Mariana Fonseca; Daryna Kurban; Jean-Philippe Roy; Débora E. Santschi; Elouise Molgat; Simon Dufour (Journal of Dairy Science)
ABSTRACT: Microbial infections of the mammary gland often cause mastitis, and it can lead to substantial economic losses within the dairy industry due to its direct negative impact on milk production and composition and the associated treatment costs. Somatic cell count has emerged as a critical indicator in monitoring udder health, and recently, the large-scale availability of differential cell count analysis potentially offers new insights into underlying physiological processes. Therefore, the main objective of this study was to estimate the variation of differential SCC (DSCC) and SCC of individual quarter-level milk samples of cows according to (1) their intramammary infectious status; (2) parity of the cow; (3) quarter location; and (4) DIM at the time of sampling. A convenience sample of 5 dairy herds using an automated milking system was selected and visited every 2 wk for milk sample collection. The determination of SCC and DSCC was performed by Lactanet using a CombiFoss 7 DC instrument. The bacteriological culture was performed according to the National Mastitis Council standards. The different types of colonies (up to 10 colonies) were counted and identified using MALDI-TOF. Given the hierarchical structure of the data, a 4-level, linear mixed model with herd, cow, and quarter as random intercepts was built with either SCS or DSCC as the outcome. Differential SCC varied broadly in the SCS range 2 to 12 but tended to have a narrower variation at higher SCS levels. The effect of DIM on DSCC depended on the parity. Early in lactation, primiparous cows tended to have lower DSCC than older cows. Following 230 DIM, the DSCC in primiparous exhibited an upward trend, whereas, in older cows, it tended to decline. The quarter position did not affect either DSCC or SCS. Quarters infected with Staphylococcus chromogenes, Streptococcus dysgalactiae, Staphylococcus aureus, Staphylococcus epidermidis, “other major,” and “other minor,” had an increase in DSCC by ∼10.2%, 9.9%, 9.8%, 9.2%, 6.0%, and 4.9%, respectively, when compared with quarters with no growth. Our findings highlighted that IMI, parity, and DIM influenced DSCC. Therefore, these parameters should be considered when interpreting DSCC.